BETRAYAL IN ROWLING’S ‘HARRY POTTER AND THE HALF BLOOD PRINCE’ - Rantung, Gabriela; Oroh, Elizabeth Z.; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The betrayal committed by a character named Professor Severus Snape. The writer believed that through this research it could contribute to the reader’s understanding of what betrayal is, and also they could better understand why it was not good to commit an act of betrayal through this story from Professor Severus Snape, how a character named Professor Severus Snape did betrayal and the causes of it. Qualitative research was used in this study because the writer collects the data in the form of words. No formulas, diagram, or numbers in this research. In analyzing this research the writer used psychological approach, because this research was focused on itself. The results shows that there is a betrayal committed by Professor Snape whics not something commendable, whatever the reason or basis for Professor Snape’s betrayal is unacceptable. Novel Harry Potter and the Half-blood Prince is an exciting novel, which is not only able to entertain, but also can make a picture for the reader to become a better person. Therefore, this novel should be read and studied further so that the values contained in it can be revealed more deeply.